2009
DOI: 10.1111/j.1442-2050.2008.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy of the esophagus in gastroesophageal reflux disease: are we losing sight of symptoms? Another perspective

Abstract: Gastroesophageal reflux disease (GERD) is an extremely common chronic disorder associated with impaired quality of life and huge economic burden. Recently, an International Consensus Group developed a global definition of GERD (The Montreal Definition): a condition that develops when the reflux of stomach contents causes troublesome symptoms and/or complications. The traditional endoscopy-based classification of GERD patients into one of three groups - non-erosive reflux disease, erosive esophagitis, and Barre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, these results should be seen in the context of an emerging consensus that de-emphasizes the utility of endoscopy or other invasive testing in the diagnosis of reflux disease [8,320]. The resulting guidelines were published about 5 years ago and may thus not be reflected in reports of diagnostic approaches that cover a longer time period.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, these results should be seen in the context of an emerging consensus that de-emphasizes the utility of endoscopy or other invasive testing in the diagnosis of reflux disease [8,320]. The resulting guidelines were published about 5 years ago and may thus not be reflected in reports of diagnostic approaches that cover a longer time period.…”
Section: Discussionmentioning
confidence: 85%
“…Alternative tests, such as ambulatory pH studies, similarly have relatively low sensitivity and specificity [5][6][7]. Five years ago, a consensus conference thus concluded that 'GER[D] is a symptom-based diagnosis, and hence symptom evaluation will remain the primary means by which treatment decisions are made for patients with suspected GER[D]' [8]. However, diagnostic testing remains a common and even increasing practice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…When symptoms persist, the PPI can be stopped for 1 week after which esophagogastroduodenoscopy, 24 h esophageal and gastric pH metry and Helicobacter pylori testing are performed to confirm erosive esophagitis or NERD. Although endoscopy with biopsy is probably the best diagnostic method, endoscopy for all patients is impractical and a symptom-based approach to patients with predominant GERD-like symptoms has been proposed [63]. In patients not responding to a PPI (correctly used), it is important to question whether they should be on or off a PPI for 24 h pH metry.…”
Section: Unmet Need Of Current Delayed Release-proton Pump Inhibitorsmentioning
confidence: 99%
“…[17][18][19][20][21] Acid, weakly acidic reflux, and visceral hypersensitivity all cause heartburn, but do not respond in the same way to acid-reducing therapies. Extra-esophageal symptoms of GERD do not respond with the same regularity to PPIs and surgery as heartburn.…”
mentioning
confidence: 96%